Method for depositing p-type layer on nitride film containing InGaN layer

By alternately deposition of p-type layers by low-temperature and high-temperature MOCVD processes on the InGaN-containing nitride film, the problem of difficult to simultaneously increase the crystallographic quality of the InGaN layer and the hole concentration of the p-type layer is solved, and the working efficiency of nitride semiconductor components is improved effect.

CN119170718AInactive Publication Date: 2024-12-20NANCHANG UNIV +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411667045.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When preparing nitride films containing InGaN layer, high deposition temperature of p-type layer in conventional methods will lead to a decrease in crystallographic mass of InGaN layer, while lowering the temperature will lead to a decrease in hole concentration and mobility of p-type layer, making it difficult to maintain high crystal mass at the same time. and high hole concentration.

Method used

The p-type layer is deposited by alternating low-temperature and high-temperature MOCVD processes. The first process deposition temperature is 750 ℃-850 ℃, and the second process deposition temperature is 920 ℃-1050 ℃. The waiting time of the InGaN layer is reduced through alternating high-low-temperature processes. Reduce carbon atom concentration and maintain high hole concentration and mobility.

Benefits of technology

It effectively alleviates the problem of crystal quality degradation of the InGaN layer, reduces the concentration of carbon atoms in the p-type layer, and improves the working efficiency of nitride semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170718A_ABST
    Figure CN119170718A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of semiconductor material preparation, and particularly relates to a method for depositing a p-type layer on a nitride film containing an InGaN layer. According to the method, in a deposition chamber of MOCVD (Metal Organic Chemical Vapor Deposition) deposition equipment, a p-type layer is deposited on a to-be-deposited surface of an InGaN layer-containing nitride film by alternately adopting a first process and a second process, and the p-type layer comprises a first p-type layer formed by the first process and a second p-type layer formed by the second process. According to the method, a low-temperature and slow-rate and high-temperature and fast-rate alternate deposition mode is adopted, under the same p-type layer deposition thickness requirement, the waiting time of the InGaN layer at a high environment temperature is shortened, the atomic diffusion problem of the InGaN layer is relieved, the concentration accumulation problem of carbon atoms caused by low-temperature deposition of the p-type layer is reduced, and the performance of the device is improved. The concentration of carbon atoms in the p-type layer is greatly reduced, so that the p-type layer has high hole concentration and high hole mobility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of semiconductor material preparation, and specifically relates to a method for depositing a p-type layer on a nitride film containing an InGaN layer. Background Art

[0002] In the field of visible light applications, nitride films containing InGaN layers are the main materials for making basic semiconductor components such as light-emitting diodes, laser diodes, and photodetectors. Currently, commercial nitride films containing InGaN layers are mainly prepared by metal-organic chemical vapor deposition (MOCVD), and the InGaN layer is deposited first and the p-type layer is deposited later. The deposition temperature of the p-type layer is much higher than that of the InGaN layer.

[0003] Generally speaking, the higher the crystal quality of the InGaN layer, the higher the hole concentration of the p-type layer, and the higher the hole mobility of the p-type layer, the higher the working efficiency of the corresponding nitride semiconductor element. However, in the above conventional material preparation mode, there is an irreconcilable contradiction: if the p-type layer is deposited at a conventional temperature, the crystallographic quality of the InGaN layer will decrease; if the high crystallographic quality of the InGaN layer is to be maintained, the ambient temperature during the deposition of the p-type layer is usually required to be reduced as much as possible, and the decrease in the ambient temperature during deposition is likely to lead to a decrease in the hole concentration and hole mobility of the p-type layer.

[0004] The direct causes of the above contradiction are: 1. The bond energy of InGaN material is weak. Within the conventional p-type layer deposition temperature range, In atoms are easily diffused in the InGaN layer as the ambient temperature rises, resulting in a large number of point defects, which leads to a decrease in crystallographic quality; 2. When depositing the p-type layer, the carbon atoms in the acceptor dopant organic group are easily incorporated into the crystal lattice of the p-type layer as the ambient temperature drops. Due to the donor characteristics of carbon atoms and their destructive effect on the crystal lattice, the hole concentration and hole mobility in the p-type layer decrease. Summary of the invention

[0005] The purpose of the embodiments of the present application is to provide a method for depositing a p-type layer on a nitride film containing an InGaN layer, which can solve the problem that a decrease in ambient temperature during deposition easily leads to a decrease in the hole concentration and hole mobility of the p-type layer.

[0006] In order to solve the above technical problems, this application is implemented as follows: In a first aspect, an embodiment of the present application provides a method for depositing a p-type layer on a nitride film containing an InGaN layer, comprising the following steps: In a deposition chamber of an MOCVD deposition device, on a to-be-deposited surface of a nitride film containing an InGaN layer, a first process and a second process are alternately used to deposit a p-type layer, wherein the p-type layer includes a first p-type layer formed by the first process and a second p-type layer formed by the second process; The parameters of the first process are: deposition temperature of 750°C-850°C, deposition rate of 0.01 nm s -1 -0.03 nms -1 The acceptor dopant flux produces an acceptor atom concentration of 5×10 19 cm -3 -5×10 20 cm -3 ; The parameters of the second process are: deposition temperature of 920 °C-1050 °C, deposition rate of 0.04 nm s -1 -0.10nms -1 , the flow rate of the acceptor dopant introduced is less than 10% of the flow rate of the acceptor dopant in the adjacent first process; The deposition thickness of the first p-type layer is greater than the deposition thickness of the adjacent second p-type layer; The deposition thickness of the first p-type layer is 5.0 nm-20.0 nm.

[0007] The present invention can protect the InGaN quantum well and maintain a low carbon atom concentration in the p-type layer through the above process method. The principle is as follows: In the above process, under the condition that the required p-type layer thickness and acceptor atom concentration remain unchanged, most of the time is used for the growth of the low-temperature p-type layer, which reduces the waiting time of the InGaN layer at high temperature, greatly alleviates the problem of crystal quality degradation of the InGaN layer, and uses a small amount of time for the second p-type layer process, eliminating the accumulation of carbon-containing groups in the reaction chamber, so that the overall carbon concentration of the p-type layer is low. In addition, when the second p-type layer process is carried out, if the growth rate is too slow, it is easy to cause the carbon-containing groups in the reaction chamber to be adsorbed on the crystal surface and incorporated into the crystal lattice. Therefore, it is necessary to maintain a faster growth rate, such as 0.1 nm s -1 If the growth is 1 nm, the second p-type process lasts for 10 s. During this 10 s, if the flow rate of the acceptor dopant is zero, the concentration of carbon-containing groups in the reaction chamber can be greatly reduced. Therefore, the purpose of "greatly reducing the concentration of carbon-containing groups in the reaction chamber" needs to be achieved before the next first p-type layer process is carried out. Therefore, the time of the second p-type layer process in the present invention is preferably short, but a sufficient growth rate should be considered to prevent the carbon-containing groups from adsorbing on the surface, and it should be as thin as possible. If it is thick, it will cause large fluctuations in the doping concentration in the entire p-type layer, which is not conducive to the uniform distribution of hole concentration.

[0008] Based on the above principles, the alternating growth requirements of "low temperature, high temperature, high acceptor dopant flow, low acceptor dopant flow, thick, thin" of the present invention are unified, and the lack of one of them will inevitably bring disadvantages.

[0009] If the deposition temperature of the second process in the above process is lower than 920°C, even if the growth rate is high, it is easy to cause the carbon-containing groups in the reaction chamber to be incorporated into the crystal lattice; and if the deposition temperature is higher than 1050°C, even if the duration is short, it will cause great damage to the crystal quality of the InGaN layer contained in the film. If the temperature in the first process is lower than 750°C, a large number of point defects will be formed in the p-type layer deposited by the first process, causing a significant decrease in the crystal quality of the p-type layer. Therefore, the deposition temperature of the present invention is very important.

[0010] The setting of the acceptor dopant flow rate in the above second process is mainly due to the accumulation effect of the acceptor dopant in the MOCVD reaction chamber, and the acceptor atoms will diffuse in the nitride film, so in the alternating growth process, the acceptor atoms in the already grown material will diffuse into the currently grown material; in order to eliminate the concentration of gas-phase carbon-containing groups in the environment, the acceptor dopant flow rate must be greatly reduced. Therefore, when the acceptor dopant grows at a low flow rate, the acceptor atom concentration in the material will not be greatly reduced with a significant reduction in the flow rate, so the above parameter range is the most suitable range for the present invention.

[0011] Optionally, the number of InGaN layers in the above-mentioned nitride film containing InGaN layers is greater than 1, and the thickness of each InGaN layer is 0.5 mm-5.0 mm.

[0012] Optionally, the In content in each of the above InGaN layers is 15%-45%.

[0013] Optionally, the acceptor dopant includes magnesiumocene.

[0014] Optionally, the raw material transport gas in the first process and the second process is nitrogen.

[0015] Optionally, the deposition thickness of the second p-type layer is 1.0 nm-10.0 nm.

[0016] Optionally, the number of alternations is greater than 2 times.

[0017] Optionally, the number of layers of the first p-type layer is multiple layers, and the parameters of the first process corresponding to the multiple layers of the first p-type layer are not completely the same; The second p-type layer has multiple layers, and the parameters of the second process corresponding to the multiple layers of the second p-type layer are not completely the same.

[0018] In a second aspect, an embodiment of the present application provides a nitride semiconductor element prepared by the above-mentioned deposition method.

[0019] In a third aspect, embodiments of the present application provide for application of the above-mentioned nitride semiconductor elements in light-emitting diodes, laser diodes, photodetectors and solar cells.

[0020] Beneficial effects of the present invention: The present invention adopts a first process and a second process to deposit the p-type layer alternately, wherein the first process adopts a low temperature and slow rate deposition method for depositing the p-type layer, and the second process adopts a high temperature and fast rate deposition method, so under the same p-type layer deposition thickness requirement, the waiting time of the InGaN layer in a higher ambient temperature is reduced, the atomic diffusion problem of the InGaN layer is alleviated, and the concentration accumulation problem of carbon atoms in the MOCVD reaction chamber caused by the low temperature deposition of the p-type layer is reduced, so that the carbon atom concentration in the p-type layer is greatly reduced, the p-type layer has a high hole concentration and a high hole mobility, and the working efficiency of the nitride semiconductor element prepared by the method is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 This is a schematic diagram of the deposition process when a p-type layer is deposited on the surface of a nitride film containing an InGaN layer provided in some embodiments of the present application; wherein 10 is a nitride film containing an InGaN layer; 11 is a first p-type layer; 12 is a second p-type layer, and 13 is a p-type layer; and D is a deposition direction.

[0023] Figure 2 These are the mass spectrometry curves of the acceptor atom magnesium (Mg) and the impurity atom carbon (C) in the p-type layer prepared in Example 1 of the present application; wherein (a) corresponds to Example 1, (b) corresponds to Example 1 of the present application, (c) corresponds to Example 3, and (d) corresponds to Example 4. The ×-shaped point data corresponds to the concentration of magnesium (Mg) atoms, and the circular point data corresponds to the concentration of carbon (C) atoms.

[0024] Figure 3 This is a curve showing the change in internal quantum efficiency of the yellow light emitting diode prepared in Example 1 of the present application as a function of current density; wherein the cross-shaped data corresponds to Example 1, the solid triangle data corresponds to Example 2, and the hollow circle data corresponds to Example 1 of the present application. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] In conjunction with the accompanying drawings, the deposition method and application of the p-type layer in the nitride film containing the InGaN layer provided in the embodiment of the present application are described in detail through specific embodiments and application scenarios.

[0027] In a first aspect, the present application provides a method for depositing a p-type layer on a nitride film containing an InGaN layer, comprising the following steps: In a deposition chamber of an MOCVD deposition device, on a to-be-deposited surface of a nitride film containing an InGaN layer, a first process and a second process are alternately used to deposit a p-type layer, wherein the p-type layer includes a first p-type layer formed by the first process and a second p-type layer formed by the second process; The parameters of the first process are: deposition temperature of 750°C-850°C, deposition rate of 0.01 nm s -1 -0.03 nms -1 The acceptor dopant flux produces an acceptor atom concentration of 5×10 19 cm -3 -5×10 20 cm -3 ; The parameters of the second process are: deposition temperature of 920 °C-1050 °C, deposition rate of 0.04 nm s -1 -0.10nms -1 , the flow rate of the acceptor dopant introduced is less than 10% of the flow rate of the acceptor dopant in the adjacent first process; The deposition thickness of the first p-type layer is greater than the deposition thickness of the adjacent second p-type layer; The deposition thickness of the first p-type layer is 5.0 nm-20.0 nm; Beneficial effects: (1) The present invention uses a low-temperature deposition method for part of the p-type layer, and uses a fast-rate deposition method for the p-type layer deposited at a high temperature. Therefore, under the same p-type layer deposition thickness requirement, the waiting time of the InGaN layer in a higher ambient temperature is reduced, and the atomic diffusion problem of the InGaN layer is alleviated; (2) Since the carbon atoms in the acceptor dopant organic group have a cumulative effect in the MOCVD reaction chamber, the present invention adopts a high temperature deposition method with a low acceptor dopant concentration after the low temperature deposition process, which can greatly alleviate the accumulation problem of carbon atoms in the MOCVD reaction chamber, thereby reducing the probability of carbon atoms being incorporated into the material lattice and greatly reducing the carbon atom concentration in the material; (3) The present invention adopts a method in which a high-concentration acceptor dopant is deposited in a thick thickness and a low-concentration acceptor dopant is deposited in a thin thickness, which can ensure that the deposited p-type layer as a whole has a higher acceptor atom concentration.

[0028] In some embodiments, the number of InGaN layers in the above-mentioned nitride film containing an InGaN layer is greater than 1, and the thickness of each InGaN layer is 0.5 mm-5.0 mm. In the method of the present invention, since the InGaN layer will produce material degradation during the long-term high-temperature p-layer growth process, the thickness of each InGaN layer is set to 0.5 mm-5.0 mm.

[0029] In some embodiments, the In content of each InGaN layer is 15%-45%. When the In content in the method of the present invention is lower than 15%, the degree of degradation of the InGaN layer due to high temperature is less, and the role played in the present invention is smaller; when the In content is higher than 45%, the degree of degradation of InGaN is greater, and conventional application devices rarely use such InGaN layers, resulting in less applicability of the present invention. Therefore, the In content is best within the range of 15%-45%, and the method of the present invention has a more significant effect on the crystal quality protection of the InGaN layer.

[0030] In some embodiments, the acceptor dopant includes magnesium cyclopentadienyl.

[0031] In some embodiments, the raw material transport gas in the first process and the second process is nitrogen. In the present invention, hydrogen is not used as the raw material transport gas during the low-temperature deposition process, because the hydrogen in the environment will enhance the accumulation effect of carbon atoms in the MOCVD reaction chamber. Using nitrogen as the raw material transport gas can alleviate the accumulation problem of carbon atoms in the MOCVD reaction chamber, thereby reducing the probability of carbon atoms being incorporated into the material lattice and reducing the carbon atom concentration in the material.

[0032] In some embodiments, the deposition thickness of the second p-type layer is 1.0 nm-10.0 nm.

[0033] In some embodiments, the number of alternations is greater than 2 times.

[0034] In some embodiments, the number of layers of the first p-type layer is multiple layers, and the parameters of the first process corresponding to the multiple layers of the first p-type layer are not completely the same; The second p-type layer has multiple layers, and the parameters of the second process corresponding to the multiple layers of the second p-type layer are not completely the same.

[0035] In a second aspect, the present application provides a nitride semiconductor component prepared by the above-mentioned deposition method.

[0036] The present invention overcomes the disadvantages of conventional p-type layer deposition methods that high hole concentration, high hole mobility and high InGaN layer crystal quality are difficult to obtain simultaneously by using a p-type layer deposition method that alternately uses a "low deposition temperature, slow deposition rate, thick deposition thickness and high acceptor dopant concentration" process and a "high deposition temperature, fast deposition rate, thin deposition thickness and low acceptor dopant concentration" process, thereby improving the working efficiency of related nitride semiconductor components.

[0037] In a third aspect, the present application provides the application of the above-mentioned nitride semiconductor element in light-emitting diodes, laser diodes, photodetectors and solar cells.

[0038] Example 1 A method for depositing a p-type layer on a nitride film containing an InGaN layer, which specifically comprises the following steps: The nitride film 10 containing the InGaN layer is placed in a deposition chamber of an MOCVD device, triethylgallium is used as a gallium element donor, ammonia is used as a nitrogen element donor, bismuthocene magnesium is used as an acceptor dopant, and nitrogen is used as a raw material transport gas. On the surface of the nitride film 10 containing the InGaN layer, a first p-type layer 11 is deposited by a first process and a second p-type layer 12 is deposited by a second process, and the p-type layer 13 is obtained by alternating 8 times in a deposition direction D. The parameters of the first process are: deposition temperature of 780 °C and deposition rate of 0.01 nm s -1 , the deposition thickness is 10nm, the flow rate of acceptor dopant is 500sccm, and the concentration of acceptor atoms is 2.3×10 20 cm -3 ; The parameters of the second process are: deposition temperature of 940 °C and deposition rate of 0.10 nm s -1 , the deposition thickness is 2 nm, and the acceptor dopant flow rate is 10 sccm; In this embodiment, there are 8 alternations, and in each alternation, the first process or the second process uses the same process parameters.

[0039] Example 2 A method for depositing a p-type layer on a nitride film containing an InGaN layer, which specifically comprises the following steps: The nitride film 10 containing the InGaN layer is placed in a deposition chamber of an MOCVD device, triethylgallium is used as a gallium element donor, ammonia is used as a nitrogen element donor, bismuthocene magnesium is used as an acceptor dopant, and nitrogen is used as a raw material transport gas. On the surface of the nitride film 10 containing the InGaN layer, a first p-type layer 11 is deposited by a first process and a second p-type layer 12 is deposited by a second process, and the p-type layer 13 is obtained by alternating three times along a deposition direction D. In this embodiment, there are three alternations, and the parameters used in the first process or the second process in each alternation are not completely the same; The parameters of the first process in the first alternating process are: deposition temperature of 780 °C, deposition rate of 0.01 nm s -1 The deposition thickness is 15 nm, the flow rate of the acceptor dopant is 500 sccm, and the concentration of the acceptor atoms produced is 2.3×10 20 cm -3 ; The parameters of the second process in the first alternating process are: deposition temperature of 940 °C, deposition rate of 0.10 nm s -1 , the deposition thickness is 5 nm, and the acceptor dopant flow rate is 10 sccm; The parameters of the first process in the second alternating process are: deposition temperature of 785 °C, deposition rate of 0.01 nm s -1 The deposition thickness is 15 nm, the flow rate of the acceptor dopant is 500 sccm, and the concentration of the acceptor atoms produced is 2.3×10 20 cm -3 ; The parameters of the second process in the second alternating process are: deposition temperature of 941 °C, deposition rate of 0.10 nm s -1 , the deposition thickness is 5 nm, and the acceptor dopant flow rate is 10 sccm; The parameters of the first process in the third alternating process are: deposition temperature of 782 °C, deposition rate of 0.01 nm s -1 The deposition thickness is 15 nm, the flow rate of the acceptor dopant is 500 sccm, and the concentration of the acceptor atoms produced is 2.3×10 20 cm -3 ; The parameters of the second process in the third alternation are: deposition temperature of 940 °C, deposition rate of 0.10 nm s -1 The deposition thickness is 5 nm and the acceptor dopant flow rate is 10 sccm.

[0040] Example 3 A method for depositing a p-type layer on a nitride film containing an InGaN layer, which specifically comprises the following steps: The nitride film 10 containing the InGaN layer is placed in a deposition chamber of an MOCVD device, triethylgallium is used as a gallium element donor, ammonia is used as a nitrogen element donor, bismuthocene magnesium is used as an acceptor dopant, and nitrogen is used as a raw material transport gas. On the surface of the nitride film 10 containing the InGaN layer, a first p-type layer 11 is deposited by a first process and a second p-type layer 12 is deposited by a second process, and the p-type layer 13 is obtained by alternating three times along a deposition direction D. In this embodiment, there are three alternations, and completely different parameters are used in the first process or the second process in each alternation; The parameters of the first process in the first alternating process are: deposition temperature of 780 °C, deposition rate of 0.01 nm s -1 The deposition thickness is 15 nm, the flow rate of the acceptor dopant is 500 sccm, and the concentration of the acceptor atoms produced is 2.3×10 20 cm -3 ; The parameters of the second process in the first alternating process are: deposition temperature of 940 °C, deposition rate of 0.10 nm s -1 , the deposition thickness is 5 nm, and the acceptor dopant flow rate is 10 sccm; The parameters of the first process in the second alternating process are: deposition temperature of 785 °C, deposition rate of 0.02 nm s -1 The deposition thickness is 16 nm, the acceptor dopant flow rate is 870 sccm, and the acceptor atom concentration is 2.0×10 20 cm -3 ; The parameters of the second process in the second alternating process are: deposition temperature of 941 °C, deposition rate of 0.08 nm s -1 , the deposition thickness is 6 nm, and the acceptor dopant flow rate is 9 sccm; The parameters of the first process in the third alternating process are: deposition temperature of 782 °C, deposition rate of 0.03 nm s -1 The deposition thickness is 17 nm, the flow rate of the acceptor dopant is 1370 sccm, and the concentration of the acceptor atoms is 2.1×10 20 cm -3 ; The parameters of the second process in the third alternating process are: deposition temperature of 942 °C, deposition rate of 0.07 nm s -1 The deposition thickness is 7 nm and the acceptor dopant flow rate is 5 sccm.

[0041] Comparative Example 1 A method for depositing a p-type layer on a nitride film containing an InGaN layer, which specifically comprises the following steps: The nitride film containing the InGaN layer was placed in the deposition chamber of the MOCVD equipment, triethylgallium was used as the gallium donor, ammonia was used as the nitrogen donor, bismuth magnesium was used as the acceptor dopant, and nitrogen was used as the raw material transport gas. The parameters were "deposition temperature of 820 °C, deposition rate of 0.01 nm s -1 , the deposition thickness is 100nm, the flow rate of the acceptor dopant is 500sccm, and the concentration of the acceptor atoms produced is 2.0×10 20 cm -3 " process to deposit the p-type layer; The p-type InGaN thin films prepared in Comparative Example 1 and Example 1 were subjected to atomic mass spectrometry test, and the curve comparison results are as follows: Figure 2 As shown, the acceptor atom is a magnesium (Mg) atom; It can be seen that under the condition of the same concentration of acceptor atom magnesium (Mg), the carbon (C) atom concentration in Comparative Example 1 is 2.0×10 16 to 1.0×10 18 cm -3 range, and has obvious surface accumulation phenomenon, while the carbon (C) atomic concentration in Example 1 of the present invention is only 1.0×10 16 to 1.0×10 17 cm -3 Range, no obvious surface accumulation phenomenon.

[0042] The comparison results of the internal quantum efficiency versus current density curves of the yellow light emitting diodes prepared by the p-type InGaN thin films prepared in Comparative Example 1 and Example 1 are as follows: Figure 3 As shown; It can be seen that the maximum value of the internal quantum efficiency of the light-emitting diode in comparative example 1 is comparable to the maximum value of the internal quantum efficiency of the light-emitting diode in Example 1 of the present invention, but Example 1 has a higher internal quantum efficiency at a high current density, which indicates that the p-type layer of the light-emitting diode in Example 1 of the present invention can provide a larger hole current, that is, the hole concentration in the p-type layer is higher.

[0043] Comparative Example 2 A method for depositing a p-type layer on a nitride film containing an InGaN layer, which specifically comprises the following steps: placing the nitride film containing the InGaN layer in a deposition chamber of an MOCVD device, using triethylgallium as a gallium element donor, ammonia as a nitrogen element donor, bismuth magnesium as an acceptor dopant, and nitrogen as a raw material transport gas, on the surface of the nitride film containing the InGaN layer, using parameters such as "deposition temperature of 940 ° C, deposition rate of 0.01 nm s-1 , the deposition thickness is 100 nm, the flow rate of the acceptor dopant is 500 sccm, and the resulting acceptor atom concentration is 2.0×10 20 cm -3 " process to deposit the p-type layer; The comparison results of the internal quantum efficiency versus current density curves of the yellow light emitting diodes prepared by the p-type InGaN thin films prepared in Comparative Example 2 and Example 1 are as follows: Figure 3 As shown; It can be seen that the maximum value of the internal quantum efficiency of the light-emitting diode in comparative example 2 is lower than that of the light-emitting diode in embodiment 1 of the present invention, which indicates that the InGaN light-emitting layer crystal quality of the light-emitting diode in embodiment 1 of the present invention is higher, that is, the degree of degradation of the InGaN light-emitting layer crystal quality caused by the high ambient temperature of the p-type layer is smaller. The internal quantum efficiency of the yellow light-emitting diode obtained in comparative example 2 at a high current density is higher than that of comparative example 1, because there is a higher concentration of carbon atoms in the p-type layer of the light-emitting diode in comparative example 1.

[0044] Comparative Example 3 A method for depositing a p-type layer on a nitride film containing an InGaN layer, which specifically comprises the following steps: The nitride film containing the InGaN layer is placed in a deposition chamber of an MOCVD device, triethylgallium is used as a gallium element donor, ammonia is used as a nitrogen element donor, bismuthocene magnesium is used as an acceptor dopant, and nitrogen is used as a raw material transport gas. On the surface of the nitride film containing the InGaN layer, a p-type layer is deposited by a first process and the entire film is annealed by a second process, and the process is alternated 8 times in sequence to obtain a complete p-type layer; The parameters of the first process are: deposition temperature of 780 °C and deposition rate of 0.01 nm s -1 The deposition thickness is 12 nm, the flow rate of the acceptor dopant is 460 sccm, and the concentration of acceptor atoms is 2.1×10 20 cm -3 ; The parameters of the second process are: ambient temperature of 940 °C, zero metal organic source flow rate, zero deposition thickness, zero acceptor dopant flow rate, and duration of 20 s. Except for the metal organic source, ambient temperature, and duration, the other process parameters are the same as those of the first process. In this comparative example, 8 alternations were performed, and the same process parameters were used in the first process or the second process in each alternation; The p-type InGaN thin films prepared in Comparative Example 3 and Example 1 were subjected to atomic mass spectrometry test, and the curve comparison results are as follows: Figure 2 As shown, the acceptor atom is a magnesium (Mg) atom; It can be seen that under the condition of the same concentration of acceptor atom magnesium (Mg), the carbon (C) atom concentration in Comparative Example 3 is 2.0×10 16 to 1.0×10 18 cm -3 range, and showed a slow accumulation trend, while the carbon (C) atomic concentration in Example 1 of the present invention was only 1.0×10 16 to 1.0×10 17 cm -3 The results show that if the high-temperature growth step is not added and only the high-temperature waiting is performed, it is not possible to effectively prevent the carbon-containing groups in the gas phase from being adsorbed and accumulated on the surface of the p-type layer, which will cause the carbon atom concentration to gradually increase.

[0045] Comparative Example 4 A method for depositing a p-type layer on a nitride film containing an InGaN layer, which specifically comprises the following steps: The nitride film containing the InGaN layer is placed in a deposition chamber of an MOCVD device, triethylgallium is used as a gallium element donor, ammonia is used as a nitrogen element donor, bismuthocene magnesium is used as an acceptor dopant, and nitrogen is used as a raw material transport gas, and a first process is used to deposit a p-type layer and a second process is used to deposit a second p-type layer on the surface of the nitride film containing the InGaN layer, and the process is alternated three times in sequence to obtain a complete p-type layer; The parameters of the first process are: deposition temperature of 780 °C and deposition rate of 0.01 nm s -1 The deposition thickness is 30 nm, the flow rate of the acceptor dopant is 480 sccm, and the concentration of the acceptor atoms is 2.2×10 20 cm -3 ; The parameters of the second process are: deposition temperature of 940 °C and deposition rate of 0.1 nm s -1 , the deposition thickness is 2 nm, and the acceptor dopant flow rate is 10 sccm; In this comparative example, there are three alternations, and the first process or the second process uses the same process parameters in each alternation; The p-type InGaN thin films prepared in Comparative Example 4 and Example 1 were subjected to atomic mass spectrometry test, and the curve comparison results are as follows: Figure 2 As shown, the acceptor atom is a magnesium (Mg) atom; It can be seen that under the condition of the same concentration of acceptor atom magnesium (Mg), the carbon (C) atom concentration in Comparative Example 4 is 4.0×10 16 Up to 2.0×10 19 cm -3 range, and presents a staged accumulation phenomenon, while the carbon (C) atomic concentration in Example 1 of the present invention is only 1.0×10 16to 1.0×10 17 cm -3 range, and the carbon atom concentration is uniform; this result shows that there is an effective range of thickness in the first p-type layer process. If the effective range is exceeded, the carbon-containing groups in the environment cannot be effectively prevented from being incorporated into the lattice during the deposition of the low-temperature p-type layer, resulting in a higher carbon atom concentration.

[0046] Therefore, in summary, the present invention uses most of the time for the growth of the low-temperature p-type layer under the condition that the required p-type layer thickness and the acceptor atom concentration remain unchanged, thereby reducing the waiting time of the InGaN layer at high temperature, greatly alleviating the crystal quality degradation problem of the InGaN layer, and using a small amount of time for the second p-type layer process, eliminating the accumulation of carbon-containing groups in the reaction chamber, so that the overall carbon concentration of the p-type layer is low, thereby achieving the effect of protecting the InGaN quantum well and maintaining a low carbon atom concentration in the p-type layer.

[0047] The embodiments of the present application are described above in conjunction with the accompanying drawings. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the core idea of ​​the present application, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the inspiration of the present application, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present application and the claims, all of which are within the protection of the present application.

Claims

1. A method for depositing a p-type layer on a nitride film containing an InGaN layer, It is characterized in that The method comprises the following steps: In a deposition chamber of an MOCVD deposition device, on a to-be-deposited surface of a nitride film containing an InGaN layer, a first process and a second process are alternately used to deposit a p-type layer, wherein the p-type layer includes a first p-type layer formed by the first process and a second p-type layer formed by the second process; The parameters of the first process are: deposition temperature of 750°C-850°C, deposition rate of 0.01 nm s -1 -0.03 nms -1 The acceptor dopant flux produces an acceptor atom concentration of 5×10 19 cm -3 -5×10 20 cm -3 ; The parameters of the second process are: deposition temperature of 920°C-1050°C, deposition rate of 0.04 nm s -1 -0.10nms -1 , the flow rate of the acceptor dopant introduced is less than 10% of the flow rate of the acceptor dopant in the adjacent first process; The deposition thickness of the first p-type layer is greater than the deposition thickness of the adjacent second p-type layer; The deposition thickness of the first p-type layer is 5.0 nm-20.0 nm.

2. The method according to claim 1, It is characterized in that The number of InGaN layers in the nitride film containing InGaN layers is greater than one.

3. The method according to claim 2, It is characterized in that The thickness of each InGaN layer is 0.5 mm-5.0 mm.

4. The method according to claim 3, It is characterized in that The content of In in each InGaN layer is 15%-45%.

5. The method according to claim 1, It is characterized in that In the first process and the second process, the raw material transport gas is nitrogen.

6. The method according to claim 1, It is characterized in that The deposition thickness of the second p-type layer is 1.0 nm-10.0 nm.

7. The method according to claim 1, It is characterized in that The number of alternations is greater than 2 times.

8. The method according to claim 7, It is characterized in that The first p-type layer has multiple layers, and the parameters of the first process corresponding to the multiple first p-type layers are not completely the same; The second p-type layer has multiple layers, and the parameters of the second process corresponding to the multiple layers of the second p-type layer are not completely the same.

9. A nitride semiconductor device, It is characterized in that The method is prepared by any one of claims 1 to 8.

10. The nitride semiconductor element according to claim 9 is used in light emitting diodes, laser diodes, photodetectors and solar cells.

Citation Information

Patent Citations

  • Method for manufacturing high-growth-rate LED (light-emitting diode) with P-type GaN structure

    CN102769078A

  • Method for manufacturing p-type GaN low-resistance-value ohmic contact layer

    CN104377278A

  • Growing method of light-emitting diode epitaxial wafer and light emitting diode epitaxial wafer

    CN104465898A

  • Manufacturing method of light-emitting diode epitaxial wafer and light-emitting diode epitaxial wafer

    CN105679893A

  • Nitride epitaxial structure prepared by utilizing metal substrate and preparation method thereof

    CN110429025A